Stage fright - Bently, Peter, 1960- (Vampire school, 2012)
When Miss Gargoyle's class stages "Snow Fright and the Seven Dwarfs" and the lead actress loses her voice, young vampires Lee, Bella, and Billy concoct a plan to save the day.